Usages et effets de la microsimulation dans l’élaboration d’une réforme. Un nouvel éclairage sur la création du RSA - Franck Bessis; Paul Cotton (Revue de la Régulation)
Do economists make policies? This article takes a fresh look at this classic question by seeking to understand the capacity of microsimulation evaluation to contribute to the design of a reform. Taking as our case study the creation of the Revenu de Solidarité Active (Active Solidarity Income) between 2005 and 2008, we highlight three main uses for this instrument of economic expertise and evaluation of socio-fiscal legislation. A demonstrative use of microsimulation models produces reality effects: the figures obtained make a project more concrete and credible. An exploratory use produces knowledge effects: simulating leads to the formulation of new questions and the design of innovative answers responses to the initial project. Finally, a deductive use allows us to translate the political trade-offs and saturate the resulting constraints to obtain the precise parameters of the reform. The article thus fills the gap left by a whole body of work on the creation of the RSA, which largely ignored microsimulation because it focused on the debates surrounding its experimentation and incentives.